2012
DOI: 10.17221/58/2011-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Soil macrofauna in relation to soil and leaf litter properties in tree plantations

Abstract: Soil communities exert strong influences on the processing of organic matter and nutrients. Plantations of trees, especially of nitrogen fixing ones, may affect the soil macrofauna through litter quality and quantity. This study was conducted in a randomized block design with three blocks consisting of Populus euphratica, Eucalyptus camaldulensis, Eucalyptus microtheca, Acacia farnesiana, Acacia salicina, Acacia saligna, Acacia stenophylla and Dalbergia sissoo monoculture plantations that were established in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…While an observed effect of tree species on soil communities under field conditions may just reflect variation in the microhabitat occupied by the tree species, the fact that we sampled across eucalypt microhabitats within our site (i.e., mixed and pure stands), suggests that it was likely that eucalypt species modified soil microbial communities. Few studies have investigated whether eucalypt species modify distinct microbial communities (Anderson et al 2013;Orozco-Aceves et al 2015;Sayad et al 2012). Yet, these studies support our findings by showing that eucalypt species may differentially modify both soil chemical and biotic characteristics, potentially through species varying in traits (i.e., growth rate and chemistry) related to the quantity and quality of organic matter entering soils (Baxendale et al 2014;Orwin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While an observed effect of tree species on soil communities under field conditions may just reflect variation in the microhabitat occupied by the tree species, the fact that we sampled across eucalypt microhabitats within our site (i.e., mixed and pure stands), suggests that it was likely that eucalypt species modified soil microbial communities. Few studies have investigated whether eucalypt species modify distinct microbial communities (Anderson et al 2013;Orozco-Aceves et al 2015;Sayad et al 2012). Yet, these studies support our findings by showing that eucalypt species may differentially modify both soil chemical and biotic characteristics, potentially through species varying in traits (i.e., growth rate and chemistry) related to the quantity and quality of organic matter entering soils (Baxendale et al 2014;Orwin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The genus is of economic and ecological importance and, therefore, it is important to determine what factors drive the performance of these species. While there are some reports of eucalypt species differentially influencing soil chemical properties (Orozco-Aceves et al 2015;Sayad et al 2012), there is also evidence to suggest that eucalypt species can differentially modify soil communities. For instance, Anderson et al (2013) found that E. saligna and E. sideroxylon seedlings modified distinct soil fungal communities after just five month's growth in a greenhouse experiment.…”
mentioning
confidence: 99%
“…Plants are expected to influence the presence and abundance of invertebrate ecosystem engineers, partly through variation of litter quantity and quality among plant species (Lavelle et al, 1997;Schwarz et al, 2015). Common garden experiments confirm this link; Reich et al (2005) and Sayad et al (2012) showed that variability of earthworm biomass across plantations of different tree species was positively correlated with the amount of calcium in leaf litter.…”
Section: Introductionmentioning
confidence: 99%
“…However, a synthesis of available evidence suggests that competition does not have large impacts on many taxa of soil organisms, perhaps due to spatial or temporal niche differentiation (Wardle, 2002(Wardle, , 2006; but see Giller, 1996;Deca€ ens, 2010). Several observational and experimental studies report a positive effect of resource availability on soil animal diversity (van der Wal et al, 2009;Mulder et al, 2012;Sayad et al, 2012). As the diversity of resources increases, diversity of soil animals is expected to rise due to enhanced opportunities for niche differentiation with respect to habitat use and sources of energy and nutrients (Anderson, 1978;Wardle, 2006;Coleman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The three first species are non-nitrogen-fixing tree and the others are nitrogen-fixing trees. The experimental plot layout and more information about the plantations were illustrated by Sayad et al (2012).…”
Section: Study Areamentioning
confidence: 99%